Has China's Housing Production Peaked?. Issue 1 (25th January 2021) - Rogoff, Kenneth; Yang, Yuanchen
Abstract: China's real estate has been a key engine of its sustained economic expansion. This paper argues, however, that even before the COVID‐19 shock, a decades‐long housing boom had given rise to severe price misalignments and regional supply–demand mismatches, making an adjustment both necessary and inevitable. We make use of newly available and updated data sources to analyze supply–demand conditions in the fast‐moving Chinese economy. The imbalances are then compared to benchmarks from other economies. We conclude that the real estate sector is quite vulnerable to a sustained aggregate growth shock, such as COVID‐19 might pose. In our baseline calibration, using input–output tables and taking account of the very large footprint of housing construction and real estate related sectors, the adjustment to a decline in housing activity can easily trim a cumulative 5–10 percent from the level of output over a period of years.